2011
DOI: 10.1523/jneurosci.0310-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

5-HT3AReceptor-Bearing White Matter Interstitial GABAergic Interneurons Are Functionally Integrated into Cortical and Subcortical Networks

Abstract: In addition to axons and surrounding glial cells, the corpus callosum also contains interstitial neurons that constitute a heterogeneous cell population. There is growing anatomical evidence that white matter interstitial cells (WMICs) comprise GABAergic interneurons, but so far there is little functional evidence regarding their connectivity. The scarcity of these cells has hampered electrophysiological studies. We overcame this hindrance by taking recourse to transgenic mice in which distinct WMICs expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 68 publications
5
47
0
Order By: Relevance
“…However, caution must be used in extrapolating what glial cells are capable of doing in culture conditions from what they actually do in the CNS, and we have compiled a list of glutamatergic/purinergic (Table 1) and non-glutamatergic/purinergic WM receptor expression studies (Tables 2 and 3), restricted to reports that have confirmed expression in situ using established cell markers. In addition to distinguishing types of glia, a reliable test for cell identification is essential due to the presence of neuronal populations in some WM structures (von Engelhardt et al, 2011), although this is not true for the commonly used optic nerve preparations.…”
Section: Multiple Neurotransmitters Are Present In Wmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, caution must be used in extrapolating what glial cells are capable of doing in culture conditions from what they actually do in the CNS, and we have compiled a list of glutamatergic/purinergic (Table 1) and non-glutamatergic/purinergic WM receptor expression studies (Tables 2 and 3), restricted to reports that have confirmed expression in situ using established cell markers. In addition to distinguishing types of glia, a reliable test for cell identification is essential due to the presence of neuronal populations in some WM structures (von Engelhardt et al, 2011), although this is not true for the commonly used optic nerve preparations.…”
Section: Multiple Neurotransmitters Are Present In Wmmentioning
confidence: 99%
“…Notably, the optic nerve does not contain neuronal cell bodies or synapses, although this is not the case for all WM structures (von Engelhardt et al, 2011). It is surprising that neurotransmitter-mediated signaling is prominent in the optic nerve and other WM areas studied, since neurotransmitter signaling is generally considered to be an exclusive function of neurons confined to synapses.…”
mentioning
confidence: 99%
“…In the neonatal mice, the majority of 5-HT 3A R+ cells born in the SVZ migrate to the OB along the RMS. Some of these cells exit RMS and migrate to the corpus callosum and neocortex, where they express markers of GABAergic interneurons (Inta et al, 2008;Le Magueresse et al, 2011;von Engelhardt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CCK transmission may also contribute to the 5-HT 3A receptor-mediated extinction of fear memory. It has been suggested that 5-HT 3 receptorcontaining interneurons are composed of a biochemically heterogeneous subpopulation of neurons that may be involved in different inhibitory circuits (Morales and Bloom 1997;Lee et al 2010;von Engelhardt et al 2011); however, the specific function of each subgroup in fear memory processes remains to be established. Therefore, detailed analysis based on the subgroups of 5-HT 3 receptor-expressing interneurons will provide further insight into their specific roles in the regulation of fear memory.…”
mentioning
confidence: 99%